The Role of Entrepreneurship Education in Cultivating Student’s Entrepreneurial Intention - Bayu Airlangga Putra; Hermien Tridayanti; Agus Sukoco (LPPM of NAROTAMA UNIVERSITY, 2018)
Purpose: This research seeks to prove whether entrepreneurship education can significantly grow student’s entrepreneurial intention. The approach of theory of planned behavior (TPB) is used to examine whether the effect of entrepreneurship education on student’s entrepreneurial intention initially goes through attitude variables, subjective norms, and perceptions about behavioral control first. The population of this study is the students of Narotama University who were taking the course of Strategic HR Management in the odd semester of 2017/2018. Data was analyzed using path analysis method. The result shows that entrepreneurship education has no direct effect on student’s entrepreneurial intention. As for the three elements of TPB, only attitude variable which is able to significantly mediate the influence of entrepreneurship education on student’s entrepreneurial intention. Design/methodology/approach: In this research, data in the form of respondents’ perceptions were analyzed quantitatively using path analysis method. Findings: Entrepreneurship education has no direct effect on student’s entrepreneurial intention and solely mediated by attitude of the students in order to effectively influence their entrepreneurial intention. Research limitations/implications: In this research, entrepreneurship education is seen from the learning process in one course only, not viewed holistically starting from a policy making process at the top management level of the university, the preparation of an integrated entrepreneurship curriculum, to its implementation in the learning process in each course. Also, the family background of each student was not considered as one of the determinants of their entrepreneurial intention. Practical implications: There is a need to increase affective content so that a stronger persuasive ability will be established among students to influence the norms in their social environment. Addition in psychomotor content is also needed to form more positive perception about students’ competence in doing entrepreneurial activity. Originality/value: This research combines the study of entrepreneurship education with the latest development in TPB study. This research also focuses on a population of students who are taking a certain course. Thus, the components in a learning process can be better observed. Paper type: Research paper Keyword: Entrepreneurship, Entrepreneurial Intention, Entrepreneurship Education, Theory of Planned Behavior